(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2001)
It has been shown that during the amine reaction of dioxanones the insignificant surplus of amine catalyzes the reaction. For the purpose of working out the optimal parameters of the reaction the formal kinetics of the process has been studied. It has been shown that the reaction proceeds with some self-braking.